THE BEHAVIOR OF BREEDERS IN HANDLING DAIRY FARM WASTE IN BALUNGANYAR VILLAGE LEKOK SUBDISTRICT PASURUAN REGENCY EAST JAVA PROVINCE - M, Meiliana; Inggriati, N. W. T.; Suarta, G. (Jurnal Peternakan Tropika; Vol 10 No 2 (2022): Vol. 10 No. 2 Tahun 2022; May - August, 2022)
This research aims to determine the level of knowledge, attitudes, skills, and application of farmers in dealing with dairy cattle waste and the factors related to farmer behavior. The research was conducted in Balunganyar Village, Lekok District, Pasuruan Regency from June to July 2021. The selection of research locations used the purposive sampling method , and took respondents by quota. stratified random sampling as many as 40 people. Data analysis was carried out by means of qualitative descriptive andtest Spearman's Level Correlation Coefficient. The results showed that knowledge was in the medium category, attitudes were in the positive category, skills were in the high category, application was in the low category, and behavior was in the medium category. Factors that are very significantly related to behavior are: formal education and non-formal education; The factors that are significantly related are: the number of livestock ownership, perception, and motivation; while for the age factor, the number of dependents of the family, and the number of land tenure are not significantly related to the behavior of farmers in dealing with dairy cattle waste. Conclusion: 1) Farmer behavior in dealing with dairy farm waste is classified as moderate; 2) Factors related to behavior are: formal education, non-formal education, number of livestock ownership, perception, and motivation. Suggestion: for the government to provide counseling on how to properly handle dairy farm waste, to improve the behavior of farmers in dealing with dairy farm waste. Keywords : knowledge, attitude, application, correlation, counseling